Differential gene expression in brain and peripheral tissues in depression across the life span: A review of replicated findings. (December 2016) - Ciobanu, Liliana G.; Sachdev, Perminder S.; Trollor, Julian N.; Reppermund, Simone; Thalamuthu, Anbupalam; Mather, Karen A.; Cohen-Woods, Sarah; Baune, Bernhard T.
Highlights: Genome-wide gene expression signature of depression identifies potential novel mechanisms and treatment targets. 57 brain and 21 peripheral DEGs are replicated at genome-wide level in depression. Functional overlap between brain and periphery links depression and CVD. Dermal fibroblasts are a promising experimental model for depression biomarker research. Gene PXMP2 is a proposed novel candidate for pathophysiology of depression. Abstract: There is a growing body of research investigating the gene expression signature of depression at the genome-wide level, with potential for the discovery of novel pathophysiological mechanisms of depression. However, heterogeneity of depression, dynamic nature of gene expression patterns and various sources of noise have resulted in inconsistent findings. We systematically review the current state of transcriptome profiling of depression in the brain and peripheral tissues with a particular focus on replicated findings at the single gene level. By examining 16 brain regions and 5 cell types from the periphery, we identified 57 replicated differentially expressed genes in the brain and 21 in peripheral tissues. Functional overlap between brain and periphery strongly implicates shared pathways in a comorbid phenotype of depression and cardiovascular disease. The findings highlight dermal fibroblasts as a promising experimental model for depression biomarker research, provide partial support for all major theories of depression and suggest a novel candidate gene, PXMP2, which plays a critical role in lipid and reactive oxygen species metabolism.